Pendidikan Kewirausahaan dalam Pengembangan Life Skill Peserta Didik di MA Al-Hikmah 2 Sugihwaras - Nofan; Muhammad Turmudi Abror; Abdullah Haq Al Haidary (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The development of the modern era requires educational institutions to equip students with relevant life skills so that they are able to adapt to social dynamics. Entrepreneurship education has become one of the strategic approaches in fostering creativity, independence, and problem-solving skills. This study aims to examine the implementation of entrepreneurship education in extracurricular activities, efforts to strengthen students' life skills, as well as supporting and inhibiting factors in its implementation. The research method used a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. Data analysis was carried out through data condensation, data presentation, and conclusion drawing, while data validity was strengthened through persistent observation. The results showed that entrepreneurship education was carried out every Thursday with the involvement of competent instructors despite the simple facilities. This program specifically helps develop students' independence, adaptability, and social skills through practice- and project-based learning. Strengthening efforts are carried out through potential development, creativity guidance, and the provision of challenges that stimulate students' problem-solving abilities. Supporting factors include the availability of basic facilities, the involvement of teachers according to their expertise, and student enthusiasm, while inhibiting factors include limited resources, limited time allocation and lack of expert mentors. This study contributes to providing an empirical overview of the effectiveness of extracurricular entrepreneurship activities in developing life skills, while also offering input for schools in strengthening programs through improved facilities, better time management, and the provision of professional mentors